The multi-level perspective and micromobility services - Cayetano Medina-Molina; Noemí Pérez-Macías; Laura Gismera-Tierno (Journal of Innovation & Knowledge (JIK), 2022)
The reduced environmental impact of different forms of transport will contribute to achieving more sustainable cities as a result of more responsible consumption. As a result, this study's main purpose is to clarify the way in which the system, regime and niche dynamics that make up the MLP are interrelated, when it comes to explaining the day-to-day use, or lack of use, of micromobility services. In order to meet that purpose, a QCA panel data is created for 35 European urban areas using different sources and taking Sociotechnical Transition and the Multi-Level Perspective into account, enabling transformations linked to sustainability and transition processes in the transport sector to be studied. The results show that certain system and regime conditions such as the ease of locating vehicles, parking and the affordability of these services combine to explain the daily use of micromobility. In terms of not using these services, this is determined by the interrelation of certain system conditions such as parking, accessibility, ease and affordability.
Keywords: O18; O33; 650; Micromobility; Multi-level perspective; Socio technical transitions; Two-step approach